Purification of a killer toxin from Aureobasidium pullulans for the biocontrol of phytopathogens - Moura, Vanessa S. [UNESP]; Pollettini, Flavia L. [UNESP]; Ferraz, Luriany P. [UNESP]; Mazzi, Mauricio V.; Kupper, Katia C. [UNESP] (Wiley-Blackwell, 2020)
The objectives of the present study were to purify and assess the killer toxin effect produced by Aureobasidium pullulans under casual agents of green mold (Penicillum digitatum) and sour rot (Geotrichum citri-aurantii). Initially, different methods of protein precipitation were tested. The proteolytic activity and the presence of proteins acting on cell wall receptors, beta-1,3-glucanase and chitinase were determined, and toxin purification was conducted by Sephadex G-75 gel exclusion chromatography and cellulose chromatography (medium fibers). Subsequently, purification was confirmed by polyacrylamide gel electrophoresis, and the detection of killer activity was performed in solid YEPD-methylene blue buffered with citrate-phosphate (0.1 M, pH 4.6). Toxin identification was performed by liquid chromatography-mass spectrometry. The results showed that the best protein precipitation method was 2:1 ethanol (vol/vol ethanol/supernatant). It was possible to observe the presence of enzymes with proteolytic activity, including beta-1,3-glucanase and chitinase. During the purification process, it was verified that the killer toxin produced by the yeast has a low-molecular-weight protein belonging to the ubiquitin family, which presents killer activity against P. digitatum and G. citri-aurantii.
Keywords: Geotrichum citri‐ aurantii; hydrolytic enzymes; Penicillium digitatum; ubiquitin‐ like